Use of Personal Music System: Does it Cause Hearing Loss or Tinnitus? - Geetha C.; Nazneen Gangji; Shwetha Krishnan; Rajashekar B (Journal of All India Institute of Speech and Hearing)
The present study aimed to investigate the prevalence of tinnitus and hearing problem, and the relationship between tinnitus, hearing loss and amount of music exposure in subjects using personal music system over a period of time. Eighty-nine subjects who use personal music system with head phones answered a questionnaire which contained 11 questions related to the amount of use of personal music system, tinnitus and hearingloss. Pure Tone Audiometry and Tympanometry were done in these subjects. Results revealed the prevalence of tinnitus in 20% of the subjects and hearing loss in 7.2% of subjects (either loss at 4 kHz loss and/or at 8 kHz). Further, 15.3% of the subjects with tinnitus were associated with hearing loss at 8 kHz, and the remaining 84.7% with tinnitus had normal hearing. No statistically significant differences found between the hearing thresholds of subjects with tinnitus and without tinnitus, between the groups differing in amount of exposure. It is suggested that recreational music does cause tinnitus and could be injurious to hearing. Hence, emphasis on creating awareness and educating the youngsters on the prevention of ear and hearing related problems by the use of personal music system is warranted.